1994
DOI: 10.1507/endocrj.41.99
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Acute Water Load on Plasma ANP and AVP, and Renal Water Handling in Hypothyroidism: Comparison of Before and After L-Thyroxine Treatment.

Abstract: Abstract. To assess whether atrial natriuretic peptide (ANP) and arginine vasopressin (AVP) participate in impaired water excretion in patients with hypothyroid states (HS), an oral acute water loading (WL) test (20 ml/kg.BW/45 min) was performed before and after L-thyroxine (T4) treatment in 5 hypothyroid patients. Plasma ANP, AVP, osmolality (Posm), total protein and renal water excretion were simultaneously determined, and these data were compared to the data from five normal subjects (NS). The impaired wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…In addition, our results suggested the integrity of the PRA-aldosterone axis. Most studies detect a decrease in the elimination of a water loading in hypothyroid patients, (DeRubertis et al 1971, Skowsky & Kikuchi 1978, Laczi et al 1987, Iwasaki et al 1990, Ota et al 1994) and a lower plasma osmolality than euthyroid individuals (Laczi et al 1987, Iwasaki et al 1990, Barna et al 1994, Ota et al 1994.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our results suggested the integrity of the PRA-aldosterone axis. Most studies detect a decrease in the elimination of a water loading in hypothyroid patients, (DeRubertis et al 1971, Skowsky & Kikuchi 1978, Laczi et al 1987, Iwasaki et al 1990, Ota et al 1994) and a lower plasma osmolality than euthyroid individuals (Laczi et al 1987, Iwasaki et al 1990, Barna et al 1994, Ota et al 1994.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of this hormone have been reported to be high in some hypothyroid patients, mimicking the state of inappropriate antidiuretic hormone secretion syndrome (SIADH) (Skowsky & Kikuchi 1978, Laczi et al 1987. However, more recently, plasma AVP has been found to be normal or low in hypothyroid patients (Iwasaki et al 1990, Ota et al 1994. In addition, low plasma levels of atrial natriuretic hormone (ANH) have been found in some studies (Kohno et al 1987, Zimmerman et al 1987, Woolf & Moult 1988, Vesely et al 1989, Widecka et al 1990, Barna et al 1994, Ota et al 1994.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Onthe other hand, plasma ADHhas been shown to be low, and ADHresponses to changes in plasma osmolality are attenuated in hypothyroidism (3, 7). In particular, Ota et al (3) showed that plasma ADHis decreased in hypothyroidism, but it did not decrease in response to a fall in plasma osmolality after an acute water load. These findings strongly suggest that there is impaired osmoregulation of ADHrelease and/or a decrease in the metabolic clearance rate (MCR)ofADH.…”
mentioning
confidence: 99%
“…These difficulties might be mainly due to the multiplicity of the pathophysiology in hypothyroidism, involving impaired renal and cardiovascular functions as well as distortion of hypothalamo-adrenal systems , antidiuretic hormone (ADH)and atrial natriuretic peptide (ANP) release, which play important roles in water and electrolyte metabolisms (2,3). In hypothyroidism, decreases in free water formation and urine volume, especially following an acute water load, were consistently noticed, irrespective of the presence or absence of hyponatremia (3). Diminished ability of the kidney to excrete free water fails to produce maximumurine dilution, leading to water retention with consequent hyponatremia.…”
mentioning
confidence: 99%